A systematic review and meta‐analysis of premature mortality in bipolar affective disorder. (3rd March 2015) - Hayes, J. F.; Miles, J.; Walters, K.; King, M.; Osborn, D. P. J.
<x xml:space="preserve">Abstract</x> Objective To review and complete meta‐analysis of studies estimating standardised mortality ratios (SMRs) in bipolar affective disorder (BPAD) for all‐cause and cause‐specific mortalities. Method Cause‐specific mortality was grouped into natural and unnatural causes. These subgroups were further divided into circulatory, respiratory, neoplastic and infectious causes, and suicide and other violent deaths. Summary SMRs were calculated using random‐effects meta‐analysis. Heterogeneity was examined via subgroup analysis and meta‐regression. Results Systematic searching found 31 studies meeting inclusion criteria. Summary SMR for all‐cause mortality = 2.05 (95% CI 1.89–2.23), but heterogeneity was high (I2 = 96.2%). This heterogeneity could not be accounted for by date of publication, cohort size, mid‐decade of data collection, population type or geographical region. Unnatural death summary SMR = 7.42 (95% CI 6.43–8.55) and natural death = 1.64 (95% CI 1.47–1.83). Specifically, suicide SMR = 14.44 (95% CI 12.43–16.78), other violent death SMR = 3.68 (95% CI 2.77–4.90), deaths from circulatory disease = 1.73 (95% CI 1.54–1.94), respiratory disease = 2.92 (95% CI 2.00–4.23), infection = 2.25 (95% CI 1.70–3.00) and neoplasm = 1.14 (95% CI 1.10–1.21). Conclusion Despite considerable heterogeneity, all summary SMR estimates and a large majority of individual studies showed elevated mortality in BPAD compared to the general population. This was true for all causes of mortality studied.